Tantangan Dan Strategi Pendidikan Kebencanaan Dalam Kurikulum Merdeka - Ficky Adi Kurniawan; Anggoro Budi Prasetyo; Rosynanda Nur Fauziah (Pusat Riset dan Inovasi Nasional, 2024)
Disaster education is an important focus in implementing the kurikulum merdeka in Indonesia. This research examines the challenges and strategies related to integrating disaster education into the curriculum. A survey was conducted at several schools in the Daerah Istimewa Yogyakarta. This area is vulnerable to disasters, and to understand the dynamics of disaster education at the school level. The main challenges include integrating disaster material into existing curriculum substance, the readiness of educators to deliver the material effectively, and the availability of adequate resources. In addition, public awareness, the lack of emphasis on disaster education, and the need for continuity in educational programs are also the focus of this research. The results of this research can provide in-depth insight into the challenges faced as well as strategies that can be adopted to overcome obstacles in integrating disaster education into the kurikulum merdeka. The implications of these findings can help improve and develop more effective disaster education strategies in the Indonesian educational environment.